2003
DOI: 10.1080/13576280310001607460
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Health-Related Attitude and Self-Reported Behaviour of Undergraduate Students at the American University of Beirut Following a Health Awareness Course

Abstract: The results presented herein are encouraging and indicate support for the impact of a health awareness class on knowledge, attitude, and behaviour of undergraduate students. The two topical areas that did not show improvements between pre and post assessment were those (i). for which students already scored high at pre assessment, or (ii). which the course did not tackle specifically. Conclusions to be drawn are limited by several factors inherent in the design of this evaluation. Future evaluation should incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
5
0
1
Order By: Relevance
“…The difference in the scores of the experimental and control groups was significant in relation to type of diet and nutritional habits but was not significant in relation to physical activity. This result supports the results of many of the reviewed studies [21][22][23][24] and might be attributed to that it is easier to note the direct influence on behaviours that do not require much effort such as nutrition vs. behaviours related to physical activity. However, the results of a study conducted in Beijing reflected contradictory results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The difference in the scores of the experimental and control groups was significant in relation to type of diet and nutritional habits but was not significant in relation to physical activity. This result supports the results of many of the reviewed studies [21][22][23][24] and might be attributed to that it is easier to note the direct influence on behaviours that do not require much effort such as nutrition vs. behaviours related to physical activity. However, the results of a study conducted in Beijing reflected contradictory results.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, movement in a health promotion direction along the stages of change was evident for smoking, type of diet and exercise. 24 The literature reviewed has confirmed the relationship between the lifestyles and the health status of individuals. Moreover, it reflected that nurse educators are in an ideal position to develop and provide health promotion and illness prevention programmes, both for their own nursing students and for a broader campus-wide student population.…”
Section: Literature Reviewmentioning
confidence: 88%
“…In the light of this, several studies have shown that health education has a positive effect on knowledge and attitudes towards health issues (Haghani et al, 2017;Soweid et al, 2003;Wang et al, 2015). In China, Wang et al (2015) found that middle school students who received nutrition education knew more about the nutritional content of vegetables, dairy products, beans and meat; the percentage of students who thought nutrition was important for a healthy life was higher in the educated group; and finally, this group consumed vegetables and had breakfast every day.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of Grappasoni et al [6] evaluated health risks awareness of seafarers while the studies of Grappasoni et al [7], Chowdhury et al [8] and Laraquie et al [9] studied on the STI/HIV/AIDS which is considered to be a significant infectious disease for seafarers. There are also various studies examining the health awareness of undergraduate students in many different fields [10][11][12][13][14][15][16]. All these studies on seafarers and students indicate that education and information about health issues should be given regularly.…”
Section: Introductionmentioning
confidence: 99%